Research in Banking and Finance - Hasan, Iftekhar; Hunter, W. Curt (Amsterdam ; Oxford : Elsevier, 2003)
This volume of the journal expands on the themes set in the first and second volumes. A total of fifteen theoretical and empirical studies are contained in this volume. The papers examine efficiency issues in U.S. and European equity and options markets, the cost efficiency of various depository financial institutions in foreign economies and in the U.S., and analyses related to risk in financial institutions and markets, among others. This volume features papers by a significant number of international researchers from Europe, Asia, South America, and the United States.
rpm 10/07/13
Loans
Keywords: Banks and banking; Investments; International finance